2012
DOI: 10.1186/1756-0500-5-334
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of characteristics of patients with cholelithiasis from economically deprived rural Karachi, Pakistan

Abstract: BackgroundGallstones have been regarded as one of the most expensive diseases in Gastroenterology, posing a great economic burden on developing nations. The majority of Pakistani people live in rural areas where healthcare facilities are not available or are very primitive. We aim to assess the characteristics among cholelithiasis patients from rural Karachi so that a prevention campaign can be launched in rural underprivileged settings to reduce the economic burden of this preventable disease.MethodA total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
6
10
0
1
Order By: Relevance
“…In all over the world, Gallstones are two times common in middle age females as compared to men, similar is found in our study. [21][22][23][24][25] As 100% of our patients were married so our study also proves another Study done in Australia, which showed major association between marital status and gallstone incidence. 26 The normal mean values of serum Triglycerides, Cholesterol and LDL found in our study are not in that much accordance with earlier studies of serum lipids and cholelithiasis, which showed elevated Triglycerides, Cholesterol and LDL level but the low HDL values in our study are in evidence that altered serum lipids levels is a risk factor for gallstone formation.…”
Section: Resultssupporting
confidence: 59%
“…In all over the world, Gallstones are two times common in middle age females as compared to men, similar is found in our study. [21][22][23][24][25] As 100% of our patients were married so our study also proves another Study done in Australia, which showed major association between marital status and gallstone incidence. 26 The normal mean values of serum Triglycerides, Cholesterol and LDL found in our study are not in that much accordance with earlier studies of serum lipids and cholelithiasis, which showed elevated Triglycerides, Cholesterol and LDL level but the low HDL values in our study are in evidence that altered serum lipids levels is a risk factor for gallstone formation.…”
Section: Resultssupporting
confidence: 59%
“…26.7% patients were illiterate, followed by 16.7% patients had primary level education, 21.7% patients had secondary level education. Similar findings were reported in a study that nearly 61% of the patients were illiterate and the remaining included primary (14.6%), middle (8.5%), secondary (4.9%) and post-secondary (10.9%) education (Naeem, M. et al, 2012).…”
Section: Socio-demographic Characteristics Of the Cholecystectomy Patsupporting
confidence: 89%
“…So, economically more solvent patients preferred laparoscopic method whereas low income patients preferred per-abdominal method. In a study conducted in Pakistan showed that All of the patients were from low socioeconomic status; therefore, the mean(± SD) salary was PKR.6915(± 1992) (Naeem, M. et al, 2012).…”
Section: Socio-demographic Characteristics Of the Cholecystectomy Patmentioning
confidence: 99%
“…It is one of the commonest ailments presenting to surgical units. A study reported an incidence of 9.03% [9]. Nearly 75% of the patients with gall stones are symptomless [10].…”
Section: Introductionmentioning
confidence: 99%